TAFSIRAN FIQH SYEIKH ABU BAKAR AL-ASHAARI: SATU ANJAKAN PARADIGMA - Ghazali, Nornajwa (Jurnal Syariah, 2008)
Sheikh Abu Bakar al-Asha’ari was one of the Salafi activists. Some of his views regarding Islamic law had created uneaseness to muslim society in Malaysia in the early 1960s. Therefore, this article attempts to scrutinize his views of fiqh issues as well as on his controversial fatwas and to evaluate its relevency to the current situation in Malaysia.